Roles of Vanadium and Nitrogen in Photocatalytic Activity of VN‐Codoped TiO2 Photocatalyst. (19th June 2018) - Varma, Ranjana; Yadav, Manisha; Tiwari, Kajal; Makani, Nisha; Gupta, Suraj; Kothari, Dushyant C.; Miotello, Antonio; Patel, Nainesh
Abstract: In the present manuscript, we explore the VN‐codoped TiO2 system intended to understand the role played by each dopant in synergistic enhancement in performance of TiO2 photocatalyst. The photocatalytic decomposition of organic pollutants in aqueous solution under visible light was used as a probe reaction to evaluate the performance of VN‐codoped TiO2 samples with different V and N concentrations. An optical measurement of VN‐codoped TiO2 shows considerable improved visible light absorption with increase in V‐concentration as compared to increase in N concentration, which was due to the effective narrowing of the band gap by V‐doping. The energy levels formed by N‐dopants act as the trapping centers for photogenerated holes to suppress recombination process as indicated by PL and TRPL results. It is also observed that at high V‐concentrations recombination centers are created in the form of oxygen vacancies as indicated by XPS and PL. In VN‐codoped TiO2, addition of N partially fills these oxygen vacancies to reduce the number of recombination centers and prolong the lifetime of charge carriers. Thus, V improves the visible light absorption while N reduces the recombination of electron–hole pairs, thus creating the synergistic effect to produce three times better performance than pure TiO2 . Abstract : VN‐codoped TiO2 photocatalyst was synthesized by varying V and N concentration. V improves the visible light absorption to generate large number of electron‐hole pair. Role of N is to reduce the recombination of electron‐hole pair by scavenging O vacancies. Synergetic effect created by V and N produces three times better activity than pure TiO2 .